From place attachment to sense of belonging: Promoting good citizenship through civic education - Dewantara, Jagad Aditya (Jurnal Civics: Media Kajian Kewarganegaraan, 2023)
This paper describes the importance of emphasizing a sense of belonging in civic education to foster good citizenship. Several studies indicate that a sense of belonging can help enhance citizens' participation and contribution to society. This article discusses how place attachment can aid in forming a sense of belonging and how sense of belonging can be promoted through civic education. Teachers should consider the context and needs of students in order to create relevant and meaningful learning experiences. Additionally, local wisdom and cultural ties to a place can be integrated into civic education. Therefore, in civic education, sense of belonging can be enhanced through learning experiences that are connected to familiar places or environments. Through effective and place-integrated learning, students can develop a strong sense of identity and belonging, which can enhance their participation and contribution to society and citizenship.